SELF-DEVELOPMENT NEEDS OF OFFICERS IN THE FINE ARTS DEPARTMENT - Kummag, Ploynaphat; โกวงศ์ ศรีรัฐ (Thai Interdisciplinary and Sustainability Review, 2023)
The objectives of this research were (1) to study the level of self-development needs of officers in the Fine Arts Department, (2) to compare the self-development needs of officers in the Fine Arts Department according to the demographic factor, (3) to study the relationship between work motivation-oriented factor and the self-development needs of officers in the Fine Arts Department, and (4) to study the relationship between job satisfaction-oriented factor and the self-development needs of officers in the Fine Arts Department. The sample was 305 officers in the Fine Arts Department. Data were collected by questionnaire. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, LSD, and Pearson Product Moment Correlation Coefficient. These results revealed that the level of self-development needs of officers in the Fine Arts Department was high. The level of work motivation was high whereas the level of job satisfaction was also high. The hypothesis testing showed that the differences in demographic factors, including age, position group, duration, and salary, differently affected the self-development needs of officers in the Fine Arts Department. The work motivation- oriented factor had a moderate positive relationship with the self-development needs. In addition, the job satisfaction-oriented factor had a moderate positive relationship with self-development needs.